COVID-19 and the Moment to Evaluate Tourism Euphoria, Indonesia - Luchman Hakim (Program Pascasarjana, 2020)
COVID-19 outbreak has been influenced tourism sectors in Indonesia. Many economic activity related to tourism industry was drop and many tourism worker loss jobs. In the absent of tourism activity, the natural ecosystem has opportunities to restore the degraded system caused by intensive use of tourist visitation. Traveling responsible to pandemic disease spread through the tourist movement and human physical contact. New tourism should be able to promote responsible travels through the management of visitor, reduce mass tourism and create high tourism product which are able to support economic benefits to local community, socio-cultural aspect preservation, and environmental conservation. The quality is important rather than quantity or the number of tourist. COVID-19 pandemic provides significant lesson learned for new tourism implementation in Indonesia.